Do not be fooled by appearances when N-STEMI is a TIMI 0–1 blood grade flow: Definition, prevalence, and predictive factors of total occlusion-NSTEMI. (2020) - Roumegou, Pierre; Garcia, Rodrigue; Ingrand, Pierre; Lesbordes, Matthieu; Lordet, Vincent; Christiaens, Luc; Levesque, Sebastien
No abstract available